Transparent Electrodes Consisting of a Surface‐Treated Buffer Layer Based on Tungsten Oxide for Semitransparent Perovskite Solar Cells and Four‐Terminal Tandem Applications (Small Methods 5/2020). Issue 5 (7th May 2020) - Park, Helen Hejin; Kim, Jincheol; Kim, Geunjin; Jung, Hyunmin; Kim, Songhee; Moon, Chan Su; Lee, Seon Joo; Shin, Seong Sik; Hao, Xiaojing; Yun, Jae Sung; Green, Martin A.; Ho‐Baillie, Anita W. Y.; et al.
Abstract : In article number 2000074, Jangwon Seo and co‐workers address a transparent electrode approach involving surface treatment of the buffer layer, which protects the underlying organic hole transport layer from damage due to sputtering of the transparent conducting oxide. Application of this approach to a four‐terminal tandem configuration with a silicon bottom cell is demonstrated.